COMPUTATIONAL MODELING OF GRANULAR MATERIALS - Campello, Eduardo M. B. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work presents a computational model for the simulation of dry granular materials. The approach is based on the discrete element method (DEM), using phenomenological models to describe the various forces involved. A few numerical examples are provided to illustrate the potentialities of the proposed scheme. Consistent DEM models may be a useful tool for the study of granular materials and, in broader sense, many other particle systems.